2019
DOI: 10.1186/s41043-019-0168-2
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies of families of persons with learning disability in Imo state of Nigeria

Abstract: BackgroundCoping with a relative with a learning disability could be a stressful experience for family members. The present study is aimed at exploring the coping strategies adopted by families in trying to make meaning of their situation.MethodA qualitative study design using focus group discussions (FGDs) was adopted. Ten FGD sessions were held with family members of persons with a learning disability.ResultsFindings revealed patterns of family coping to include problem-focused, emotion-focused, and spiritua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 30 publications
(23 reference statements)
0
19
1
2
Order By: Relevance
“…Our findings debunk the connotation that having a disabled family member would make someone more accepting of a disability (Chukwu et al, 2019;McConnell & Savage, 2015). Perhaps compassion fatigue arises from providing constant care on a daily basis, which can take a heavy toll both on the caregiver's mental and physical well-being.…”
Section: Discussionmentioning
confidence: 53%
“…Our findings debunk the connotation that having a disabled family member would make someone more accepting of a disability (Chukwu et al, 2019;McConnell & Savage, 2015). Perhaps compassion fatigue arises from providing constant care on a daily basis, which can take a heavy toll both on the caregiver's mental and physical well-being.…”
Section: Discussionmentioning
confidence: 53%
“…A recent study showed that families or caregivers encounter lots of emotional and psychological stress in supporting their relative with IDD in Nigeria (Chukwu et al, 2019). The reasons are linked to ignorance in society and lack of information, resulting in some of them adopting negative coping strategies such as pretending that the disabled individual does not exist, keeping the disabled person out of public view and locking the disabled person in doors (Chukwu et al, 2019). In unprecedented times like COVID‐19, Nigerian policymakers and stakeholders should develop programmes and services to assist families and caregivers of these individuals to cope as well as protecting their well‐being.…”
Section: Discussion Of Main Findingsmentioning
confidence: 99%
“…This functioning has been largely attributed to the availability of medical and social support provisions to children with disability and their parents (Mas et al 2019 ). On the other hand, studies and reports about childhood disability and the family in Africa have rather focused on the challenges faced by the family in meeting the needs of children with disability, largely as a result of non or inadequate provisions of medical and social support systems to meet their special needs (Chukwu et al 2019 ; Mas et al 2019 ; Onyedibe et al 2018 ).…”
Section: Theoretical Background: ‘Othering’ and Family-based Violencementioning
confidence: 99%